2010
DOI: 10.1088/0004-637x/715/2/724
|View full text |Cite
|
Sign up to set email alerts
|

A Close Companion Search Around L Dwarfs Using Aperture Masking Interferometry and Palomar Laser Guide Star Adaptive Optics

Abstract: We present a close companion search around sixteen known early-L dwarfs using aperture masking interferometry with Palomar laser guide star adaptive optics. The use of aperture masking allows the detection of close binaries, corresponding to projected physical separations of 0.6-10.0 AU for the targets of our survey. This survey achieved median contrast limits of ∆K ∼ 2.3 for separations between 1.2 -4 λ/D, and ∆K ∼ 1.4 at 2 3 λ/D. We present four candidate binaries detected with moderate to high confidence (9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 26 publications
0
40
0
1
Order By: Relevance
“…4 Now at Department of Astronomy, Cornell University, Ithaca, NY 14853, USA. (Bernat et al 2010), and three years of solid-state sum-frequency 589 nm laser guide star operations (Velur et al 2004;Bouchez et al 2007;Roberts et al 2008) including the demonstration of back pumping and frequency chirping techniques that increase the efficiency of photoreturn from Earth's mesospheric sodium layer (Kibblewhite 2008(Kibblewhite , 2009). PALM-241 achieved infrared K-band imaging Strehl ratios under median seeing conditions of 1.…”
Section: Introductionmentioning
confidence: 99%
“…4 Now at Department of Astronomy, Cornell University, Ithaca, NY 14853, USA. (Bernat et al 2010), and three years of solid-state sum-frequency 589 nm laser guide star operations (Velur et al 2004;Bouchez et al 2007;Roberts et al 2008) including the demonstration of back pumping and frequency chirping techniques that increase the efficiency of photoreturn from Earth's mesospheric sodium layer (Kibblewhite 2008(Kibblewhite , 2009). PALM-241 achieved infrared K-band imaging Strehl ratios under median seeing conditions of 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, various radial velocity and high spatial resolution imaging works in the literature (see also Sect. 5.5) have not revealed the presence of a second, massive object in relatively close orbits around J0045+1634, J0355+1133, J1726+1538, and J2208+2921 (Reid et al , 2006Bouy et al 2003;Bernat et al 2010;Blake et al 2010;Stumpf et al 2010). Our age estimate for J0355+1133 (120 As explained in Kirkpatrick (2005) and Cruz et al (2009), the β and γ appended to the L subtypes indicate intermediateand very low-gravity spectra, respectively.…”
Section: Hr Diagram: Ages and Massesmentioning
confidence: 65%
“…Using aperture masking interferometry and laser guide star adaptive optics of the 200-inch telescope on the Palomar Observatory, Bernat et al (2010) reported the detection of a companion candidate around J0355+1133 at a separation of 82.5 mas and 2.1:1 contrast in the K s -band, suggesting that both companion and primary have similar masses. At the distance of J0355+1133, the projected physical separation would result in 0.74 AU, and each component would have a mass of about 0.04-0.05 M (after splitting the object luminosity into two sources in Fig.…”
Section: Minimum Detectable Mass Of Astrometric Companionsmentioning
confidence: 99%
“…Next, we subtracted the mean κ CrB closure phase set from the mean β CrB closure phase set, to remove systematic errors presumably present in both data sets. From here, we fitted a binary star model to the β CrB data in two stages, following an approach similar to that of Ireland et al and Bernat et al 24,27 First, we performed a "brute force" search over a coarse parameter grid. We explore a range of three parameters: radial separation (r), position angle (θ), and contrast (η).…”
Section: Results Of the β Crb Closure Phase Modelmentioning
confidence: 99%
“…Besides unique resolved measurements of individual binary and multiple star systems, 18,24,25 there has been one high-contrast survey of stars in the Upper Scorpius moving group, 26 and another survey for companions of L-dwarfs. 27 A large portion of the first survey and all of the latter survey were carried out at with the Palomar Hale Telescope's adaptive optics system (PALAO) in the near-infrared. 28 Both have yielded new sub-stellar companion candidates.…”
mentioning
confidence: 99%